2000
DOI: 10.1046/j.1365-2249.2000.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered T cell development in human thymoma is related to impairment of MHC class II transactivator expression induced by interferon-gamma (IFN-γ)

Abstract: SUMMARYThymoma is known to contain CD4 1 CD8 1 T cells, indicating that neoplastic epithelial cells of thymoma have a function as thymic cortical epithelium. However, it has been shown that there is an impairment of CD4 1 T cell development in thymoma and that IFN-g-induced HLA-DR expression on cultured thymic epithelial cells (TEC) derived from thymoma is decreased when compared with the normal thymus. MHC class II transactivator (CIITA) is known to play a critical role in IFN-g-induced MHC II expression. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
(72 reference statements)
0
25
1
Order By: Relevance
“…26 Recent research on the regulation of HLA-DR expression has shown that class II transactivator (CIITA) is a master regulator of HLA-DR molecules, 27 and CIITA expression was downregulated in neoplastic epithelial cells of thymomas as compared with normal thymi. 28 Further, in thymomas, the proportion of CD3 + cells in the CD4 + CD8 − T-cell subset was signifi cantly correlated with HLA-DR (Fig. 3) and CIITA expression.…”
Section: Difference In T-cell Development Between the Normal Thymus Amentioning
confidence: 79%
“…26 Recent research on the regulation of HLA-DR expression has shown that class II transactivator (CIITA) is a master regulator of HLA-DR molecules, 27 and CIITA expression was downregulated in neoplastic epithelial cells of thymomas as compared with normal thymi. 28 Further, in thymomas, the proportion of CD3 + cells in the CD4 + CD8 − T-cell subset was signifi cantly correlated with HLA-DR (Fig. 3) and CIITA expression.…”
Section: Difference In T-cell Development Between the Normal Thymus Amentioning
confidence: 79%
“…These observations suggested that thymoma was responsible for the export of auto-reactive CD4 + T cells whose generation could result from defects in intra-thymic selection [12,14]. More recently, a defect of T cell regulatory function has also been described.…”
Section: Discussionmentioning
confidence: 98%
“…MG-associated TM are rich in autoreactive T cells, compared with hyperplasia MG. These autoreactive T cells are positively selected and exported to the periphery where they are activated to provide help for autoantibody-producing B cells [6,7].…”
Section: Myasthenia Gravis (Mg) Is a Prototypical Cd4mentioning
confidence: 99%